2020
DOI: 10.1111/jocd.13719
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble PD1 in pemphigus vulgaris: A useful marker for disease severity

Abstract: Background Pemphigus vulgaris (PV) is a life‐threatening autoimmune blistering disease targeting the skin and mucous membranes. Programmed cell death protein 1 (PD1) is an immune checkpoint which binds to two ligands, PDL1 and PDL2 resulting in negative regulation of antigen receptor signaling, thus, play a critical role in the immune regulation of autoimmune diseases. Aim In this work we aimed to assess serum levels of soluble PD1 (sPD1) in patients with active PV and in patients in remission in an attempt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…sPD-1 is produced through proteolytic cleavage of membrane-bound forms or encoded by alternatively spliced PD-1 mRNA [ 55 ].The soluble protein participates in the blood system and mediates certain immune functions. Several autoimmune disorders, such as rheumatoid arthritis [ 56 ], immune thrombocytopenia [ 57 ], systemic juvenile idiopathic arthritis [ 58 ] and pemphigus vulgaris [ 59 ] have been implicated with a defect in the PD1 pathway, whereby lower serum sPD1 levels were correlated negatively with the severity of the disease. This could be due to sPD-1 exhibiting ‘agonism’ with its functions similar to the membrane form in the regulation of immunity by inhibiting T-cell responses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sPD-1 is produced through proteolytic cleavage of membrane-bound forms or encoded by alternatively spliced PD-1 mRNA [ 55 ].The soluble protein participates in the blood system and mediates certain immune functions. Several autoimmune disorders, such as rheumatoid arthritis [ 56 ], immune thrombocytopenia [ 57 ], systemic juvenile idiopathic arthritis [ 58 ] and pemphigus vulgaris [ 59 ] have been implicated with a defect in the PD1 pathway, whereby lower serum sPD1 levels were correlated negatively with the severity of the disease. This could be due to sPD-1 exhibiting ‘agonism’ with its functions similar to the membrane form in the regulation of immunity by inhibiting T-cell responses [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several autoimmune disorders, such as rheumatoid arthritis [ 56 ], immune thrombocytopenia [ 57 ], systemic juvenile idiopathic arthritis [ 58 ] and pemphigus vulgaris [ 59 ] have been implicated with a defect in the PD1 pathway, whereby lower serum sPD1 levels were correlated negatively with the severity of the disease. This could be due to sPD-1 exhibiting ‘agonism’ with its functions similar to the membrane form in the regulation of immunity by inhibiting T-cell responses [ 59 , 60 ]. From this point, our observation of a decrease in sPD-1 levels supported further that HFD induced a dysfunctional inhibitory capacity of PD-1, although the mechanisms involved need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…9 While this case is consistent with the hypothesis that blistering lesions that begin secondary to ICI use may be due to B-cell activation and nonspecific autoantibodies against tumor antigens, it suggests that these antibodies may also target desmosome antigens. Interestingly, serum levels of soluble PD1 have been shown to correlate inversely with PV disease severity, suggesting a defect in the PD1 pathway plays a role in PV 10 . It is possible that BP presents more frequently than PV as an ICI-related toxicity due to the relatively more exposed location of hemidesmosomes at the DEJ compared to desmosomes, which increases the frequency of BP antigen exposure and subsequent antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serum levels of soluble PD1 have been shown to correlate inversely with PV disease severity, suggesting a defect in the PD1 pathway plays a role in PV 10 . It is possible that BP presents more frequently than PV as an ICI-related toxicity due to the relatively more exposed location of hemidesmosomes at the DEJ compared to desmosomes, which increases the frequency of BP antigen exposure and subsequent antibody formation.…”
Section: Case Reportmentioning
confidence: 99%
“…Another study byHsu et al showed that hypertension was significantly associated with PV (OR=2.15;95%CI=1.25-3.71) 10. The certain correlation between PV and hypertension remains unclear, but Zeid et al suggested that serum levels of programmed cell death protein 1 (PD1) were significantly lower in PV patients than in healthy controls (p<0.001) 11. Programmed cell death protein 1 (PD1), also known as CD279, is a major inhibitory receptor that is preferentially expressed on the surfaces of T and B cells 12.…”
mentioning
confidence: 99%